Finska krigsbarn i Norrbotten - Lundmark Åström, Jennifer (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
This essay is about the children who came from Finland to the province of Norrbotten in northern Sweden during World War II, how local communities came to help Finnish warchildren and the experiences of Finnish war-children in northern Sweden during the latter part of the twentieth century. This will be investigated by the help of the social affinity theory, that comes with solidarity with people and places experienced as “close”. The social affinity theory helps explaining why Sweden was inclined to help Finland during World War II. The essay includes three interviews, two with war children, and one with a child of a war child that came to stay in Sweden after the war.